2021
DOI: 10.1126/sciadv.abi8178
|View full text |Cite
|
Sign up to set email alerts
|

A brain proteomic signature of incipient Alzheimer’s disease in youngAPOEε4 carriers identifies novel drug targets

Abstract: Brain proteins altered in young APOE ε4 carriers are found decades later in Alzheimer’s disease and present novel drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 165 publications
0
22
0
Order By: Relevance
“…However, they also have been directly implicated in brain aging phenotypes and neurodegeneration. A recent proteomic analysis also showed differential abundance of protein tyrosine kinases in the ROSMAP brain study between APOE ε4 carriers and non-carriers, and implicated these as key candidates for molecular intervention in incipient AD [ 68 ]. Gated ion channels are of clear physiological relevance to the brain—however, recent evidence further suggests that reduced neural activation may protect the aging brain [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they also have been directly implicated in brain aging phenotypes and neurodegeneration. A recent proteomic analysis also showed differential abundance of protein tyrosine kinases in the ROSMAP brain study between APOE ε4 carriers and non-carriers, and implicated these as key candidates for molecular intervention in incipient AD [ 68 ]. Gated ion channels are of clear physiological relevance to the brain—however, recent evidence further suggests that reduced neural activation may protect the aging brain [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is some intriguing data derived from human biomaterials that show APOE activates the ERK1/2 MAP kinases via dual leucine-zipper kinase (DLK) [ 47 ]. Another report investigated proteomic profile of young APOE4 carriers where several kinases related to tau phosphorylation, such as atypical protein kinase C (aPKC) PKC-ι, mitogen-activated protein kinase 12 (MAPK12), a member of the p38 MAPK family, Src family tyrosine kinases FYN, and Ca2+/calmodulin (CaM)-dependent protein kinase II (CaMKII) were identified [ 48 ]. Taken together, a gap in our knowledge remains whether APOE is functionally related to cellular metabolism that influences tau phosphorylation or facilitates intercellular transfer of tau or both in AD and related dementias.…”
Section: Discussionmentioning
confidence: 99%
“…Green: The CELF1 locus was associated with AD in genome-wide association studies (Ref. [3][4][5][6]. Red: Transcriptomic studies using CELF1 knockdown revealed strong regulation of KLC1 by CELF1; cross-linking and immunoprecipitation sequencing identified KLC1 RNA as a binding partner of the CELF1 protein and revealed its binding site.…”
Section: Fig 6 Hypothesis-free Omics Approaches Identified a Molecula...mentioning
confidence: 99%
“…As a result, there has been precipitous increase in the number of associated loci and genes identified whose function in disease is unknown 1 . Many researchers have suggested that the innovative use of functional omics will be crucial to interpret GWAS results and reveal molecular pathways in complex diseases in the post-GWAS era, but concrete strategies are still being explored 1,2,3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation